PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI KANTOR INSPEKTORAT DAERAH KABUPATEN TOJO UNA-UNA - Dinda, Kurnia Satria (Katalogis, 2017)
The study focuses on determining and analyzing the influence of competency and career development on officials’ performance in The Office of Inspectorate, Tojo Una-Una District. Population consists of 43 officials who selected through census method. Data processing uses Statistical Product and Service Solution (SPSS 18.0) with multiple linear regressions as the method of analysis. From the test, the study finds that: 1) competency and career development simultaneously have significant influence on officials’ performance in The Office of Inspectorate, Tojo Una-Una District; 2) competency significantly influences officials’ performance in The Office of Inspectorate, Tojo Una-Una District; 3) career development significantly influence officials’ performance in The Office of Inspectorate, Tojo Una-Una District.